Life Satisfaction, Subjective Wealth, and Adaptation to Vulnerability in the Russian Federation during 2002-2017 - Hai-Anh H. Dang; Kseniya Abanokova; Michael M. Lokshin (Global Labor Organization (GLO), 2020)
We offer the first study on vulnerability adaptation to subjective well-being, using rich panel data over the past two decades for Russia. We found no adaption to vulnerability for life satisfaction and subjective wealth, with longer vulnerability spells being associated with more negative subjective welfare. Similar results hold for other outcomes including satisfaction with own economic conditions, work contract, job, pay, and career. Some evidence indicates that despite little differences between urban and rural areas with life satisfaction, rural areas exhibit a stronger lack of adaptation for subjective wealth, particularly for longer durations of vulnerability. Higher education levels generally exhibit a stronger lack of adaptation. The lack of adaptation to vulnerability is, however, similar at different education levels for subjective wealth. We also find a U-shaped relationship between age and durations of vulnerability and disability to have the most negative impacts on life satisfaction and subjective wealth.
Keywords: D6; I3; O1; 330; vulnerability; adaptation; satisfaction; subjective wealth; gender; panel data; Russia